2014
DOI: 10.1111/pde.12435
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Use of Oral Propranolol and Topical Timolol for Infantile Hemangiomas: Survey Results and Comparison with Propranolol Consensus Statement Guidelines

Abstract: Oral and topical β-blockers are used to treat infantile hemangiomas (IHs). Although a recent consensus report provided guidelines for the treatment of IH with propranolol, there are no standard guidelines for the use of topical timolol. The objectives of this study were to determine the current use of oral propranolol and topical timolol by pediatric dermatologists in an outpatient setting and to compare current propranolol use with published propranolol consensus guidelines. An electronic survey was sent to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…On starting treatment, children less than or equal to 8 weeks gestational age should be admitted for monitoring, while all other children should be monitored with heart rates and blood pressures obtained at baseline and 1 and 2 hours after commencing treatment or after a dose increase. Kumar's survey of pediatric dermatologists found that, despite the consensus recommendations, 75% of clinicians used variations in dose, monitoring, history, and examination (21) .…”
Section: A N U S C R I P Tmentioning
confidence: 98%
See 1 more Smart Citation
“…On starting treatment, children less than or equal to 8 weeks gestational age should be admitted for monitoring, while all other children should be monitored with heart rates and blood pressures obtained at baseline and 1 and 2 hours after commencing treatment or after a dose increase. Kumar's survey of pediatric dermatologists found that, despite the consensus recommendations, 75% of clinicians used variations in dose, monitoring, history, and examination (21) .…”
Section: A N U S C R I P Tmentioning
confidence: 98%
“…Bonifazi first published the use of 1% propranolol ointment for six superficial hemangiomas in 2008, while Pope and Chakkittakaniyil began to use topical timolol maleate 0.5% gel, in 2009 (3,37) . A recent survey of pediatric dermatologists showed that 91% of those surveyed use topical timolol, 66% in conjunction with oral propranolol (21) . We review the use of topical beta blockers in the treatment of infantile hemangiomas.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Although the published data seem to demonstrate the clinical efficacy of topical PR, therapeutic protocols and guidelines have not yet been established. Indeed, the results of clinical studies published in the literature are ambiguous due to the empirical choice of semi-solid bases other than the differences in clinical protocols (e.g., study design, selection of patients, and end points) [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The frequency of dosing varied, with 31% of respondents dosing twice daily, 55% three times daily and 16% at other intervals. Only about half the responders monitored haemodynamic parameters 1–2 h after the initial dose (56%) and after each dose escalation (49%) …”
Section: Discussionmentioning
confidence: 99%